THE EFFECT OF FREE CASH FLOW ON THE FIRM VALUE IN A SAMPLE OF IRAQI COMMERCIAL COMPANIES LISTED IN THE IRAQI STOCK EXCHANGE - Hashim Hayder Yousef; Assist. Prof. Dr. Hassnain Kazem Ojah (American Journals, 2022)
The research aims to measure the impact of free cash flow on the value of the Firm. This goal is achieved by identifying the concept of free cash flow and the concept of Firm value, based on the annual financial reports data for a sample of the (27) Iraqi companies listed on the Iraq Stock Exchange. B (15) companies from the banking sector, (8) companies from the industrial sector, and (4) companies from the insurance sector for the period from (2011-2020).